AKULTURASI HUKUM ISLAM DAN BUDAYA LOKAL - Puji Kurniawan (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
Legal changes connected with the community takes two forms, the first law to adjust to changes in society (social change) in this case the law is passive, the second law of moving society toward a planned change, the law serves as a tool of social engineering / tool engineering community, in the context of this law is active